Reports of the proportion of older people living in long‐term care: a cautionary tale from New Zealand - Joanna B. Broad; Toni Ashton; Thomas Lumley; Martin J. Connolly (Elsevier, 2013)
Abstract Objective: Population ageing is driving many countries to review health and social care policies. For many, an important component is residential long‐term care (LTC). This study uses New Zealand to ascertain the extent different reports provide consistent and accurate estimates of LTC use. Methods: We searched for available cross‐sectional information about use of LTC by people aged 65 years or over in NZ's population since 1988. In addition, for one geographic region, Auckland, we compared research survey data at three time‐points with the nearest census estimates. Results: Fifty‐eight national‐level estimates (census, subsidy payments and population surveys) were found. Since 2000, estimates of the proportion of older people reportedly living in long‐term care ranged from 3.4% to 9.2%. Comparisons with Auckland studies demonstrated improved reporting in the 2006 census. Conclusion: Estimates of the proportion of people living in residential LTC varied widely. OECD reports, often used for cross‐national comparisons, were particularly inconsistent. Implications: While estimates of the proportion of people living in residential LTC in NZ are inconsistent, improvements are evident in census and subsidy data. Reconciling new data with previous reports prior to publication may reduce variations in reporting. Improved reliability will assist understanding of within‐country trends and international comparisons, and better inform decisions shaping health services for older people.